Should I stay or should I switch? : An analysis of transitions between modes of vocational education and training - Latina, Joelle [Verfasser] (My University, 2017)
"How established is the horizontal permeability between modes of vocational education and training (VET) in Switzerland? Formally encouraged by the Swiss law on VET, horizontal permeability refers to transitions across VET modes, i.e. between dual and school-based VET. This paper first discusses why horizontal permeability is indeed relevant and then empirically examines the horizontal permeability of the Swiss VET system for a given occupation - commercial VET. The latter is the largest VET domain in Switzerland and, importantly, a domain in which school-based VET is well established. The empirical analysis uses panel data following a cohort for over 10 years in the Canton of Geneva. Results show that going from school-based to dual VET within commercial VET increases chances to earn a qualification, however students changing modes lose half a year in the process. These findings suggest that, at least in commercial VET, horizontal permeability is only partial." (author's abstract; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 1.3 Berufliche Erstausbildung; S 1.3.3 Vollzeitschulische Berufsausbildung; I 2.2.1 Westeuropa; Duales System; Berufsausbildung; Übergang; Schulische Berufsausbildung; Vollzeitschule; Durchlässigkeit im Bildungssystem; Schweiz